Assessing the causes of breeding failure among the rough-legged buzzard (Buteo lagopus) during the nestling period - Pokrovskiy, Ivan; Ehrich, Dorothee; Ims, Rolf Anker; Kulikova, Olga; Lecomte, Nicolas; Yoccoz, Nigel (Polar Research, 2012)
When food becomes scarce, the youngest nestlings in facultatively siblicidal raptor species typically die and such events are usually attributed to siblicide. Here we present results from an investigation in the Arctic tundra, in which rough-legged buzzard (Buteo lagopus) breeding success was monitored with regular visits to nests and time-lapse cameras that continuously recorded the activity of chicks and their parents. The study took place in the Nenetsky Nature Reserve (68°20´N, 53°18´E) in the Russian Arctic, in 2007-10. It included 26 cases of chick mortality in 19 nests. The camera monitoring led us to discover instances of scavenging of chicks that had died due to starvation or bad weather in two nests. Camera monitoring also led us to discover how a sequence of abrupt weather shifts, between hot and sunny conditions and heavy rain, probably caused the death of nestlings in two nests. Detailed nest monitoring is required to avoid the mistaken attribution of such deaths to siblicide. Such extreme weather events may become more common with climate change and represent a new potential factor affecting roughlegged buzzards breeding success in the southern Arctic.